High‐resolution stable isotope profiles from shells of the land snail Placostylus reveal contrasting patterns between snails originating from New Zealand and New Caledonia - Mathieu Quenu; Emily J. Judd; Mary Morgan‐richards; Steven A. Trewick; Katherine Holt; Jonathan Tyler; Andrew M. Lorrey (Journal of Quaternary Science, 2023)
The stable oxygen (δ 18 O shell ) and carbon (δ 13 C shell ) isotope ratios retrieved from the carbonate shell of terrestrial gastropods can be used as an environmental proxy and are thought to reflect dietary composition and ambient climatic conditions (e.g. precipitation amount, humidity, temperature). Here, we generate high‐resolution isotopic profiles of nine modern land snails of the genus Placostylus , collected from two locations in New Caledonia and one location in New Zealand. We found that snails from New Zealand had, on average, higher δ 18 O shell values than their counterparts in New Caledonia, which surprisingly runs counter to the expected relationship based on the isotopic composition of rainwater between these two regions. Specimens from New Caledonia exhibit ephemeral decreases in their δ 18 O shell values, which could be linked to extreme precipitation events in this region, while snails from New Zealand have less variation in their δ 18 O shell values. Snails from New Zealand had, on average, slightly higher δ 13 C shell than their counterparts in New Caledonia, but a large difference in carbon isotopes was sometimes observed between snails collected at the same location. Most snails exhibit a temporal trend in their δ 13 C shell values, indicating potential shifts in diet through to maturity.

Generation of large mitochondrial and nuclear nucleotide sequences and phylogenetic analyses using high-throughput short-read datasets for endangered Placostylinae snails of the southwest Pacific - Mathieu Quenu; Steven A. Trewick; Elizabeth E. Daly; Mary Morgan-Richards (Molluscan Research, 2021)